ANALYSIS LEXICAL COHESION IN WRITTEN BY BARACK OBAMA - Sheni, Ibadadilah; Satria, Robby (BASIS (Bahasa dan Sastra Inggris), 2024)
Abstract In this modern era, many people use written and unwritten language communication tools. Therefore, language has various types in its use, one of which is lexicon cohesion. The purpose of this study, thus researchers and readers are more familiar with what lexicon is, the types and can understand more. In this study, the researchers analysed the type of lexicon cohesion, namely repetition, synonym, antonym, meronym, and hyponym using a data search from written text when the 44th President of the United States, Barack Obama made a speech. Then, researchers used the theory of Halliday and Matthiessen. The method used is the observation technique. Where the researcher collects data by reading the entire text, then the highlighted the data in the form of text related to phenomena and analysing data according to the category. The data presented is in qualitative form. Where the data is presented in the form of sentences that are not in the form of numbers, percentage, or graph. In this study, researchers read, interpret data according to theory and calculate the results obtained. The results obtained are repetition data 2, synonym 6 data, Antonym 4 data, Meronym 5 data and Hyponym data 2. The highest data is obtained with synonyms, where the writing has many synonym meanings, and the lowest is the use of repetition. Keyword: Lexical Cohesion, Repetition, Synonym, Antonym, Meronym, Hyponym